Upper Gastrointestinal Malignancy among Dyspepsia Patients in Cipto Mangunkusumo Hospital Jakarta - Ali Imron Yusuf; Ari Fahrial Syam; Murdani Abdullah; Dadang Makmun; Marcellus Simadibrata; Chudahman Manan; Abdul Aziz Rani (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2009)
Background: Upper gastrointestinal (GI) malignancy was still a health problem in all over the world. The prevalence of the upper GI malignancy vary among Asian countries. Data from Indonesia was scarcely reported. The aim of this study is to determine the frequency of upper GI malignancy among dyspepsia patients who underwent esophagoduodenoscopy (EGD) procedure. Method: This is a retrospectives study from subject with dyspepsia that had underwent upper GI endoscopy at the Department of Internal Medicine Cipto Mangunkusumo hospital from January 2005 to December 2007. All complete data from medical report and histopathology appearance will be recorded. Results: Out of 2,116 subjects underwent endoscopy due to dyspepsia, 110 (5.19%) subjects was diagnosed as cancer. This upper GI malignancy consisted of gastric cancer in 63 (2.97%) cases, esophageal cancer 32 (1.51%) and duodenal cancer 15 (0.71%). The mean ages of the subjects was 53.36 ± 10.97 years, age less than 45 years was 20 (18.20%) subjects, more than 45 years was 90 (81.18%), male 71 (64.50%) subjects, female 39 (35.50%). Most of them had alarm signs 96 (87.30%). Histopathology finding showed adeno-carcinoma in 75 (68.20%) cases, signet ring cell carcinoma in 14 (12.70%), squamous cell carcinoma in 8 (7.30%), others in 13 (11.80%). Out of 59 gastric cancer, 48 (76.20%) cases was located at distal part while the rest 11 (17.50%) cases was located at the proximal gaster, and 4 (6.30%) in diffuse. By the ethnics founded Javanese 37 (33.60%) subjects, Betawinese 22 (20.00%), Sundanese 12 (10.90%) and Batak 13 (11.80%). Conclusions: Upper GI malignancy was found in five percent of subjects with dyspepsia who undergo colonoscopy. The three most frequent malignancies were gastric carcinoma, esophageal carcinoma, and duodenal carcinoma respectively. Most of gastric adenocarcinoma was located at distal stomach. Keywords: upper gastrointestinal malignancy, dyspepsia, endoscopy, alarm sign, histopathology